Unraveling fairness in simple games? The role of empathy and theory of mind - Florian Artinger; Filippos Exadaktylos; Hannes Koppel; Lauri Sääksvuori (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Economists have been theorizing that other-regarding preferences influence decision making. Yet, what are the corresponding psychological mechanisms that inform these preferences in laboratory games? Empathy and Theory of Mind (ToM) are dispositions considered to be essential in social interaction. We investigate the connection between an individual's preference type and her disposition to engage in empathy and ToM in neutrally framed Dictator and Ultimatum Game. For that purpose, cognitive and emotional psychometric scales are applied to infer the dispositions of each subject. We find that a disposition for empathy does not influence the behavior in the games. ToM positively correlates with offers in the Dictator Game. Integral to ToM are beliefs about others. Both, other-regarding and selfish types, show a strong correlation between what they belief others do and their own action. These results indicate that expectations about the prevalent social norm might be central in informing behavior in one-shot games.
Keywords: C91; C72; D01; D03; D64; 330; Altruism; Inequality; Empathy; Theory of Mind; Behavioral Economics